The Sangamonian Stage and the Laurentide Ice Sheet - St-Onge, Denis (Géographie physique et Quaternaire, 1987)
ABSTRACTThis review of the most recent studies (up to June 1986) dealing with the Sangamonian in some key areas clearly indicates that, as yet, there is no definitive answer to the question : "When did the ice which eventually became the Laurentide Ice Sheet begin to accumulate?" In most areas the stratigraphic record simply identifies a probable interglacial period; the record yields no information on when ice growth may have started following that warm climatic interval. However the deltaic glacial lake sediments of the Scarborough Formation in the Toronto area and the Bécancour Till in the Trois-Rivières area are thought to possibly date from the Sangamonian (marine isotope sub-stages 5d-b). The Adam Till in the James Bay Lowland may be correlative. In Atlantic Canada, mostly in Cape Breton Island, plant fossils suggest a mid-Sangamonian climate roughly comparable to that which prevailed 11-12 ka ago. On Baffin Island a marine transgression of mid-Sangamonian age is thought to result from important ice accumulation in the area. These stratigraphic interpretations suggest significant glacier expansion in several areas of the North American continent during part of the Sangamonian Stage. Whether or not any of this ice survived a warmer climate period near the end of the Sangamonian to become part of the Laurentide Ice Sheet is a matter of speculation.